A single-center experience of central nervous system tumors in children under three years old - Wang, Junhua; Wang, Chuanwei; Huang, Zhimin; Zhang, Zhihua; Zhang, Yuqi (Frontiers in Pediatrics, 2024)
Purpose This study aims to summarize the characteristics of children under three years old (≤3 years) with central nervous system (CNS) tumors and to investigate the factors that influence their overall survival (OS) time. Methods We treated 171 pediatric patients (≤3 years) with CNS tumors at Yuquan Hospital of Tsinghua University from January 2016 to June 2023. Of these, 162 cases were successfully followed up. Kaplan–Meier survival analysis and Cox regression were utilized to evaluate factors potentially influencing OS of malignancies. Results There was a male predominance among the patients. The three most common tumors were embryonal tumors, gliomas, and craniopharyngiomas. Gross total resection (GTR) was achieved in select cases. Patients with high-grade malignancies were advised to undergo chemotherapy and/or radiotherapy after surgery. Optic gliomas and diffuse midline gliomas were partially resected and treated with adjuvant treatments. The median survival time of low-grade malignant tumors was 41.5 months, while that of high-grade malignant tumors was 15 months. Kaplan–Meier survival analysis identified the factors potentially influencing OS of malignancies: extent of resection, CNS WHO grade, grade of malignancies, and Ki-67 labeling index (Ki-67 LI). Subsequent multivariate analysis highlighted the interactive factor (extent of resection × CNS WHO grade) along with Ki-67 LI, as the most significant variables. Factors such as sex, age, tumor location, and onset-to-treatment time appeared not to affect OS. Conclusions GTR remains the cornerstone of treatment for children (≤3 years) with CNS tumors, except for optic glioma, diffuse midline glioma, and germinoma. The interactive factor (extent of resection × CNS WHO grade) and Ki-67 LI are the most significant factors affecting OS. The implementation of preoperative neoadjuvant chemotherapy and early postoperative chemotherapy may enhance prognosis.